Fabrication of Cordierite Ceramic Foam Filter by Replication Method - Ria Julyana Manullang; Maulid purnawan; Dede Taufik; Ayu Ratnasari; Karlina Noordiningsih (Balai Besar Keramik, 2021)
Ceramic foam filter (CFF) is widely used to improve the quality of molten metal prior to casting. Cordierite is one of the most commonly used materials for making CFF. In this research, the fabrication of cordierite-based CFF by a replication method using a polyurethane template has been studied. Waterglass and polymethacrylic acid (PMAA) were used as defloculants to synthesize ceramic suspensions. CFF was made from kaolin, talc, alumina with a defloculant concentration of 0.3% which is sintered at a temperature of 1300 - 1350oC. The experimental results showed that the porosity obtained for all CFF samples were above 70%. The best shape of CFF was obtained by using PMAA as defloculant. However, CFF did not reach the maximum strength yet so it is necessary to carry out further research on the CFF body composition.